TINJAUAN KONSEP NAFKAH DI ERA DIGITAL DALAM PERSPEKTIF IMAM SYAFI‘I - Muhyiddin Muhyiddin (Faculty of Sharia and Law UNISNU Jepara, 2020)
AbstractThis study aims to examine how Imam Shafi'i conceptualizes a living in terms of the aspect of the obligation to provide a living, the types of income that must be provided, and the level of livelihood. Then examine whether the concept is still relevant in the digital era. This study uses a type of qualitative literature research and a normative approach, the data sources used are primary sources in the form of Kitab al-Umm, and secondary sources in the form of books and journals related to livelihoods and the digital era, as well as the Marriage Law and the Compilation of Islamic Law. Data collection method used is documentation, and data analysis using descriptive and inductive. The results of this study state that, First, according to Imam Shafi'i, it is the husband who is obliged to provide a living. The types of livelihood that must be provided at a minimum are clothing, food, shelter. The level of living that must be provided is in accordance with the standard of staple food at the place of residence and adjusted to the husband's economy. One mud for a poor husband, two mud for a rich husband, and one and a half for a middle husband. Second, the opinion of Imam Syafi'i, the first regarding the obligation to earn a living is still relevant in the digital era. The second opinion about the kinds of income that must be given is irrelevant to the digital era if the husband is poor, but this opinion can be relevant if the husband is rich. The third opinion about the level of living, is still relevant to the digital era.AbstrakPenelitian ini bertujuan untuk meneliti tentang bagaimana Imam Syafi'i mengkonsepkan nafkah dalam aspek kewajiban memberi nafkah, macam-macam nafkah yang wajib diberikan, dan kadar nafkah. Kemudian meneliti apakah konsep tersebut masih relevan di era digital. Penelitian ini menggunakan jenis penelitian kualitatif kepustakaan dan pendekatan normatif, sumber data yang digunakan adalah sumber primer berupa kitab al-Umm, dan sumber sekunder berupa buku dan jurnal terkait nafkah dan era digital, serta Undang-Undang Perkawinan dan Kompilasi Hukum Islam. Metode pengumpulan data yang digunakan adalah dokumentasi, dan analisis data menggunakan deskriptif dan induktif. Hasil penelitian ini menyatakan bahwa, Pertama, menurut Imam Syafi'i, yang wajib memberi nafkah adalah suami. Macam-macam nafkah yang harus diberikan secara minimal adalah sandang, pangan, papan. Kadar nafkah yang harus diberikan sesuai dengan standar makanan pokok di tempat tinggal dan disesuaikan dengan ekonomi suami. Satu mud untuk suami miskin, dua mud untuk suami kaya, dan satu setengah mud untuk suami pertengahan. Kedua, pendapat Imam Syafi'i, yang pertama tentang kewajiban mencari nafkah masih relevan di era digital. Pendapat kedua tentang macam-macam nafkah yang harus diberikan tidak relevan dengan era digital bila suami miskin, namun pendapat ini bisa menjadi relevan bila jika suami kaya. Pendapat ketiga tentang kadar nafkah, masih relevan dengan era digital.